2008
DOI: 10.1002/rra.1050
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the channel process of a stream restoration project in an urbanizing watershed: a case study of Kelley Creek, Oregon, USA

Abstract: Pacific Northwest (PNW) streams in the United States were impacted by the 20th century development, when removal of instream structure and channelization degraded an aquatic habitat. The lower Kelley Creek in southeast Portland, USA was channelized during the 1930's Works Progress Administration (WPA) projects. Stream restoration reintroduced pool-riffle sequences and heterogeneous substrates to protect salmonids while mitigating impacts from flooding. We investigated whether the restored pool-riffle morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…), water quality (Sonoda et al . ; Sonoda and Yeakley ; Pratt and Chang ; Chen and Chang ) and ecological problems (Hook and Yeakley ; Levell and Chang ) attributable to agricultural practices and urban development in the watershed.…”
Section: Methodsmentioning
confidence: 99%
“…), water quality (Sonoda et al . ; Sonoda and Yeakley ; Pratt and Chang ; Chen and Chang ) and ecological problems (Hook and Yeakley ; Levell and Chang ) attributable to agricultural practices and urban development in the watershed.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the multi-functional ecological ponds further promoted the economic benefits to the local residents due to the overall improvement of the environment. Ecological engineering has been extensively achieved in Western countries, especially for the improvement of the water quality, habitat, and continuity of the river, as well as for the restoration of flooded areas (Mitsch et al, 2006;Levell and Chang, 2008;Morten et al, 2007;Yasuharu et al, 2005). However, these countries have focused more on the improvement of the ecosystem structure and the environment benefits, and seldom on economic benefits.…”
Section: Discussionmentioning
confidence: 98%
“…Interventions on substrate conditions must be followed by additional interventions in flow conditions in order to be successful with a more permanent effect. For example, it was observed that excessive fine sediment entry from adjacent croplands upstream of a restored system counteracted physical habitat improvements (Larson et al, 2001;Moerke et al, 2004;Levell & Chang, 2008).…”
Section: Use Of Gradients Ranking To Develop Management Plansmentioning
confidence: 97%